Advances in Dynamic Games and Their Applications Analytical and Numerical Developments - Bernhard, Pierre; Gaitsgory, Vladimir; Pourtallier, Odile (Annals of the International Society of Dynamic Games, 2009)
This book-an outgrowth of the 12th International Symposium on Dynamic Games-presents current advances in the theory of dynamic games and their applications in several disciplines. The selected contributions cover a variety of topics ranging from purely theoretical developments in game theory, to numerical analysis of various dynamic games, and then progressing to applications of dynamic games in economics, finance, and energy supply. Thematically organized into eight parts, the book covers key topics in these main areas: * theoretical developments in general dynamic and differential games * pursuit-evasion games * numerical approaches to dynamic and differential games * applications of dynamic games in economics and option pricing * search games * evolutionary games * stopping games * stochastic games and "large neighborhood" games A unified collection of state-of-the-art advances in theoretical and numerical analysis of dynamic games and their applications, the work is suitable for researchers, practitioners, and graduate students in applied mathematics, engineering, economics, as well as environmental and management sciences.